The genome sequence of the amphioxus, Branchiostoma lanceolatum (Pallas, 1774) [version 1; peer review: 2 approved] - Patrick Adkins; John Bishop; Joanna Harley; Peter W. H. Holland (Wellcome Open Research)
We present a genome assembly from a specimen of Branchiostoma lanceolatum (Amphioxus; Chordata; Leptocardii; Amphioxiformes; Branchiostomatidae). The assembly contains two haplotypes with total lengths of 468.40 megabases and 465.81 megabases, respectively. Most of haplotype 1 (99.34%) is scaffolded into 19 chromosomal pseudomolecules. Haplotype 2 is a scaffold level assembly. The mitochondrial genome has also been assembled and is 15.14 kilobases in length.